Fostering a high efficient waveguide diplexer to improve 5G network frequency spectrum for IoT devices in cloud - Alagarsamy, Gautami; J.Shanthini, Dr (International Journal of Engineering and Technology, 2018)
In recent days Internet of Things and 5G network connection are complement to each other. The 5G networks would surpass 4GLTE, 4G, 3G and the other networks we used. It has become a boon for the end users and corporate due to its architecture to handle the heavy data traffic of connected smart devices and large amount of smart phone users worldwide. 5G devices should support longer battery and available at low cost and consume less energy. Some smart phones have ability to charge wirelessly through inductive coupling between base and the phone. In advanced options for charging IoT devices Wireless deportation technology is integrated. To curb network congestion in denser areas and to operate at higher data rates in Ka band applications this research paper analyzes the impact of WR-28 Waveguide Diplexer to improve network frequency spectrum around 30GHz for IoT devices in cloud services. The design simulation and modeling are implemented by using Antenna Magus version 5.5 Software.Â Â